Stationary-phase mutants of Sinorhizobium meliloti are impaired in stationary-phase survival or in recovery to logarithmic growth. - Uhde, C (1997)
A screening method was used to identify Sinorhizobium meliloti mutants which are affected in stationary-phase survival. Of 20,000 individual colonies mutagenized with transposon Tn5-B20, 10 mutant strains which showed poor or no survival in the stationary phase were identified. Analyses of expression patterns of the promoterless lacZ genes in the mutant strains revealed individual induction patterns. Most strains were induced in stationary phase as well as under carbon limitation and in pure H2O, but none of the mutants was induced under heat, alkali stress conditions, or low oxygen tension. Plant inoculation tests revealed that the symbiotic proficiency of the mutants was not affected. Two mutants, however, showed gene induction not only in the stationary phase under free-living conditions but also in the bacteroid state. A long-term starvation test was carried out to examine the ability of the 10 mutants to survive prolonged stationary-phase conditions. All mutants showed a clear decrease in the colony-forming ability under the chosen experimental conditions. Staining with green and red fluorescent nucleic acid stain showed that the mutants fell into two different classes. Seven mutants died during stationary phase; the three other mutants remained viable but did not resume growth after prolonged starvation. Five of the ten Tn5-B20 insertions were cloned from the genomes of the mutant strains. Nucleotide sequence analyses established that the transposon had inserted in five distinctive genes. Database searches revealed that four of the tagged loci corresponded to already characterized genes whose gene products are involved in important cellular processes such as amino acid metabolism or aerobic respiration.